A study of multiobjective parametric optimisation of electric discharge diamond cut-off grinding of Inconel 718. (2016) - Unune, Deepak Rajendra; Mali, Harlal Singh
Hybrid machining techniques are becoming more and more popular for machining of difficult-to-cut materials. This paper presents an approach for the optimisation of electric discharge diamond cut-off grinding of Inconel 718 with multiple performance characteristics based on the Taguchi orthogonal array with grey relational analysis. In this study, the machining parameters namely, wheel speed, current, pulse-on-time, and duty factor are optimised for performance characteristics, i.e., material removal rate and surface roughness. The optimal machining parameters are determined by the Grey relational grade as the performance index. The research result identifies significant machining parameters and their effects on process performance. The confirmation experiments have been conducted to verify the optimal process conditions. Experimental results show that the performance of process improved effectively through this approach.